PENGARUH KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA DINAS KESEHATAN KOTA BATAM - Siti Nadiah Albantani; Asron Saputra (LPPM Universitas Putera Batam, 2022)
The purpose of this study was to determine whether communication and work discipline affect employee performance at the Batam City Health Office. This research was conducted using quantitative techniques. The population used consisted of 164 employees of the Batam City Health Office. The research sample used as many as 164 employees of the Batam City Health Office with the saturated sampling method. Questionnaires were used as a data collection technique. By using SPSS 25 software, data analysis techniques include descriptive statistical tests, data quality tests, classical assumption tests, influence tests and hypothesis testing. Based on the results of multiple linear regression, communication has an effect of 0.392 or 39.2% on employee performance (Y) at the Batam City Health Office and work discipline (X2) has an effect of 0.490 or 49.0% on employee performance (Y) at the City Health Office. Batam. Communication factors and work discipline affect employee performance (Y) at the Batam City Health Office by 71.4%, according to the data of the coefficient of determination (R2). Based on the results of the t test, communication has a partially significant effect on employee performance and work discipline has a partially significant effect on employee performance, and the f test results show that communication and work discipline simultaneously have a significant effect on employee performance (Y) at the Batam City Health Office.